2015
DOI: 10.1093/cercor/bhv202
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing VIP Neurons in the Barrel Cortex of VIPcre/tdTomato Mice Reveals Layer-Specific Differences

Abstract: Neocortical GABAergic interneurons have a profound impact on cortical circuitry and its information processing capacity. Distinct subgroups of inhibitory interneurons can be distinguished by molecular markers, such as parvalbumin, somatostatin, and vasoactive intestinal polypeptide (VIP). Among these, VIP-expressing interneurons sparked a substantial interest since these neurons seem to operate disinhibitory circuit motifs found in all major neocortical areas. Several of these recent studies used transgenic Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
217
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(270 citation statements)
references
References 48 publications
47
217
2
4
Order By: Relevance
“…It is unlikely that the fast-spiking SCs reported in our study are identical to the small and nest basket cells reported in (23), because small and nest basket cells often display an adapting regularspiking firing pattern (unlike SCs) and were observed in neocortical L2/3 and L4 (unlike SCs) (23). In adult visual cortex, we found that L5 vasointestinal peptide (VIP-cre/Ai9 mice) (24) cells were very sparse, and the few we studied did not exhibit obvious bipolar morphology as previously reported in somatosensory cortex (25). Therefore, more work is needed to study the L5 VIP types.…”
supporting
confidence: 80%
“…It is unlikely that the fast-spiking SCs reported in our study are identical to the small and nest basket cells reported in (23), because small and nest basket cells often display an adapting regularspiking firing pattern (unlike SCs) and were observed in neocortical L2/3 and L4 (unlike SCs) (23). In adult visual cortex, we found that L5 vasointestinal peptide (VIP-cre/Ai9 mice) (24) cells were very sparse, and the few we studied did not exhibit obvious bipolar morphology as previously reported in somatosensory cortex (25). Therefore, more work is needed to study the L5 VIP types.…”
supporting
confidence: 80%
“…They imply, for instance, that, other than Martinotti cells, no other interneuron types were previously described in layer 5. This is at odds with publications reporting vasointestinal peptide (VIP) bipolar interneurons in layer 5 [e.g., (6) (7)]. The authors redefine and rename interneuron types resulting in claims of novel cell classes and improper acknowledgment of much of the literature.…”
mentioning
confidence: 96%
“…This does not seem to be the case in the adult isocortex, where the Cre-driven labeling of the PV+, SST+, and VIP+ cells colocalizes in >95% cells with the expression of the respective reporter proteins (Pfeffer et al, 2013; Pronneke et al, 2015; Taniguchi et al, 2011). Similarly, subcortical PV-Cre and VIP-Cre labeling agrees well with available data for the respective mRNA and protein marker expression in the adult brain, while several thalamic and hypothalamic SST-Cre-positive areas do not appear to express SST in the adult brain, suggesting that these cell populations are indeed marked due to a transient developmental SST expression (see Anatomical Description in the STAR method).…”
Section: Discussionmentioning
confidence: 93%
“…Previous immunohistochemical studies characterized the relative laminar distribution of major interneuron cell types in the somatosensory and visual cortex (Gonchar et al, 2007; Pfeffer et al, 2013; Pronneke et al, 2015; Rudy et al, 2011; Xu et al, 2010), and our data showed that this pattern is indeed repeated across the entire isocortex: the PV+ and SST+ interneurons are most abundant in the layers 4–5 (PV+) and layers 4–6 (SST+), while the VIP+ interneurons show high density in the layers 1–4, with a peak in the layer 2/3 (Figure 3; see also Figure S5 for distribution based on distance from the brain surface).…”
Section: Resultsmentioning
confidence: 99%